2022
DOI: 10.1186/s12887-022-03413-z
|View full text |Cite
|
Sign up to set email alerts
|

LUNCH—Lung Ultrasound for early detection of silent and apparent aspiratioN in infants and young CHildren with cerebral palsy and other developmental disabilities: study protocol of a randomized controlled trial

Abstract: Background Children with neurological impairment may have dysphagia and/or gastro-esophageal reflux disease (GERD), which predispose to complications affecting the airways, increasing risk for aspiration-induced acute and chronic lung disease, or secondarily malnutrition, further neurodevelopmental disturbances, stressful interactions with their caregivers and chronic pain. Only multidisciplinary clinical feeding evaluation and empirical trials are applied to provide support to the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These aspects encourage potential applications of the LUS technique for non-invasive, infant-friendly study in fragile populations such as newborns and infants. These has been recently addressed by our group supporting the usefulness of LUS to identify pulmonary abnormalities potentially related to feeding difficulties in infants and young children with neurological impairment (8,9). In this direction, infants born preterm or newborns with other comorbidities that may impact feeding abilities may represent a potential target to promote a further use of LUS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These aspects encourage potential applications of the LUS technique for non-invasive, infant-friendly study in fragile populations such as newborns and infants. These has been recently addressed by our group supporting the usefulness of LUS to identify pulmonary abnormalities potentially related to feeding difficulties in infants and young children with neurological impairment (8,9). In this direction, infants born preterm or newborns with other comorbidities that may impact feeding abilities may represent a potential target to promote a further use of LUS.…”
Section: Discussionmentioning
confidence: 96%
“…Our research group reported previous encouraging results in detecting silent and overt inhalation related to the meal in children with cerebral palsy or other encephalopathies leading to dysphagia/gastroesophageal reflux disease (GERD) ( 8 ) and designed a randomized controlled trial in order to investigate LUS-monitored meals evaluation and feeding management in infants aged 0–6 years with neurodevelopmental delay, the LUNCH Study (ClinicalTrials.gov Identifier: NCT04253951) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%